"Jedes starre Konzept ist schlecht und passt net’ in diese Welt": Nutzen und Nachteil der Standardisierung der Beratungs- und Vermittlungsstätigkeit in der Arbeitsvermittlung - Ludwig-Mayerhofer, Wolfgang; Sondermann, Ariadne; Behrend, Olaf (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2007)
The recent reform of the Bundesagentur fijr Arbeit, Germany’s Public Employment Service (PES), has introduced elements of New Public Management, including internal controlling and attempts at standardizing assessments (’profiling’ of unemployed people) and procedures. Based on qualitative interviews with PES staff, we show that standardization and controlling are perceived as contradicting the ’case-oriented approach’ used by PES staff in dealing with unemployed people. It is therefore not surprising that staff members use considerable discretion when (re-)assigning unemployed people to one of the categories pre-defined by PES headquarters. All in all, the new procedures lead to numerous contradictions, which often result in bewilderment and puzzlement on the part of the unemployed.